2017
DOI: 10.4102/safp.v59i1.4654
|View full text |Cite
|
Sign up to set email alerts
|

A new health care profession in rural district hospitals: a case study of the introduction of Clinical Associates in Shongwe hospital

Abstract: Background: One of the reasons to develop training courses for medical mid-level workers in South Africa is a shortage of doctors. The introduction of this new profession has led to task sharing and redefining of professional boundaries. The primary aim of this study is to evaluate the introduction of new healthcare professionals in a rural hospital district. Methods: This multi-method qualitative research study used a semi-structured questionnaire to assess the effectiveness of Clinical Associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…The findings support the outcomes of the study conducted at a district hospital in Mpumalanga that looked into the introduction of ClinAs at their facility, which found that ClinAs assisted the hospital in maintaining and improving patient care. 9 The strong agreement among participants that more ClinAs will strengthen their hospitals' ability to provide the needed quality of healthcare services is evidence of the high regard for their contribution. The efficient use of HRH that include The study did not find strong agreement on the provision of putting measures in place or supported efforts to create the needed awareness for ClinAs as the new profession at hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings support the outcomes of the study conducted at a district hospital in Mpumalanga that looked into the introduction of ClinAs at their facility, which found that ClinAs assisted the hospital in maintaining and improving patient care. 9 The strong agreement among participants that more ClinAs will strengthen their hospitals' ability to provide the needed quality of healthcare services is evidence of the high regard for their contribution. The efficient use of HRH that include The study did not find strong agreement on the provision of putting measures in place or supported efforts to create the needed awareness for ClinAs as the new profession at hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a case study done in Mpumalanga, some healthcare professionals were not keen to work with ClinAs despite evidence of improved access to care for clients and a reduction in the waiting times in casualty and outpatient departments. 9 Clinical associates, together with other healthcare workers, are able to provide comprehensive healthcare to a large number of clients. A study in 2018 from the Tshwane district in South Africa found that almost 90% of circumcisions between 2014 and 2015 were done by ClinAs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, long-term disability requires sustained interactions with the medical and rehabilitative services [4,50,63]. Careful, strategic thinking on the mix of cadres, their roles, regulation, financing and training and supervision and management of teams and services are needed [64][65][66]. To inform this much more might be learned from better evaluation of existing experience.…”
Section: Implications and Future Considerationsmentioning
confidence: 99%
“…To inform this much more might be learned from better evaluation of existing experience. Governments, regulatory councils and training institutions also need to enable changes in education, legislation, policy and financing well in advance of future expansion of service scope and scale as producing the desired mix of professions and skills may take years or even decades [64,65].…”
Section: Implications and Future Considerationsmentioning
confidence: 99%
“…Students with the BCMP degree are qualified to practise as clinical associates in South Africa (SA). [11] They spend most of…”
mentioning
confidence: 99%